ENHANCING HUMAN-MACHINE INTERACTION IN INDUSTRIAL AUTOMATION: A CASE STUDY ON GP-PRO EX WITH THREELAMPBITINVERT.PRX EXAMPLE - Pandey, Chinmay; Sondhiya, Ritu Raj; Agrawal, Prashant; Singh, Vikash Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The modern industrial automation relies heavily on Human-Machine Interfaces (HMIs) to create a vital connection between operators and their machines. This paper evaluates GP-Pro EX HMI design software capabilities by analyzing the ThreeLampBitInvert.prx specific example. This paper illustrates how GP-Pro EX software enables efficient HMI development and simulation and deployment through its features which lead to operational improvements and human error reduction. The ThreeLampBitInvert.prx example demonstrates how GP-Pro EX performs complex logic operations including bit inversion through an interface which operators find easy to use. Advanced HMI solutions matter in industrial automation based on study results which open the way for integrating emerging technologies like artificial intelligence (AI) and machine learning (ML).